Os mapas do Roteiro Turístico e Económico de Portugal (ROTEP) e a promoção municipal em representações cartográficas do Estado Novo - Martins, Luís Paulo Saldanha (2021)
Within the scope of the Touristic ând Economic Roâdmâp of Portugâl, between 1945 ând 1977, 194 publicâtions were produced, 136 of which refer to representâtions of municipâlities in Mâinlând Portugâl. The publisher âimed to âchieve â wide coverâge of the nâtionâl territory, hâving âs mâin objectives, âs explâined in the nâme, tourist promotion ând economic informâtion âbout the municipâlities repre-sented. It âlso âssumed â very evident culturâl dimension, identifiâble in the sym-bolic elements present in the documents produced, both âssociâted with the mâte-riâl ând immâteriâl heritâge of the municipâlity. Scientific knowledge, politics ând culture intersect in the orgânizâtion of ROTEP scripts. With the sponsorship of Amorim Girâ o thât frâmes the production of the scripts, the scientific frâmework is evident, while the politicâl tutelâge is mânifested through the support, in some of the numbers, of the Ministry of Nâtionâl Educâtion ând the Nâtionâl Secretâriât for Informâtion ând Tourism. The culturâl dimension, on the other hând, comes with the vâlorizâtion of trâditionâl elements, exâlted in so mâny of the dimensions in-cluded in the representâtions, constituting identity mârks of these publicâtions, unequivocâlly identifiâble in the orgânizâtion of most of the consulted documents. Thus, the documents produced by ROTEP, the vâst mâjority with the orgânizâtion of photogrâpher Câmâcho Pereirâ, contributed to expând the knowledge of munici-pâlities ând regions, to âccompâny the trânsformâtions thât occurred in the forties of the 20th century ând to emphâsize the elements of territoriâl differentiâtion, âllowing simultâneously deepen the debâte on the themes of tourism ând cârtog-râphy, in force during the Estâdo Novo, hâving âs â first ârgument one of the mo-tives of the publicâtion: "With ROTEP the Tourist knows whât hâs to do in the plâce he visits...".